12. DISABILITY CHARACTERISTICS OF SCHIZOPHRENIA PATIENTS AT THE MENTAL HEALTH INSTITUTE, BACH MAI HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the characteristics of disability in schizophrenic patients at Mental Health Institute, Bach Mai Hospital.Method: A cross-sectional study.Results: The average age of schizophrenia onset was 34.42±10.85 years. The majority of patients were under 40 years old (73.3%), while those aged 40 and above accounted for 26.7%. The prevalence of schizophrenia was higher in females (56.7%) than in males (43,3%). Patients aged ≥ 40 had significantly higher disability scores in the domains of understanding and communication (6.88±6.13 vs. 3.22±4.50, p = 0.015) and social integration (6.63±4.84 vs. 3.68±3.89, p = 0.018). Patients with a history of psychiatric medication use had higher disability scores in mobility (2.82±3.20 vs. 0.56±0.73, p = 0.040), daily life activities (8.39±7.41 vs. 3.00±3.91, p = 0.038), and overall disability score (34.51±25.42 vs. 15.33±14.59, p = 0.033).Conclusion: Disability is quite common among individuals with schizophrenia. Most patients experience significant difficulties in understanding and communication, social integration, and daily life activities.
Keywords: Functional disability; functional impairment; schizophrenia